YBX1 Enhances Metastasis and Stemness by Transcriptionally Regulating MUC1 in Lung Adenocarcinoma - Xie, Qiang; Zhao, Shilei; Liu, Wenzhi; Cui, Yanwei; Li, Fengzhou; Li, Zhuoshi; Guo, Tao; Yu, Wendan; Guo, Wei; Deng, Wuguo; Gu, Chundong (Frontiers in Oncology, 2021)
Abnormal expression of the transcription factor Y-box-binding protein-1 (YBX1) is associated with the proliferation, migration, aggressiveness, and stem-like properties of various cancers. These characteristics contribute to the tumorigenesis and metastasis of cancer. We found that the expression levels of Mucin-1 (MUC1) and YBX1 were positively correlated in lung adenocarcinoma cells and lung adenocarcinoma tissue. Our retrospective cohort study of 176 lung adenocarcinoma patients after surgery showed that low expression of both YBX1 and MUC1 was an independent predictor of the prognosis and recurrence of lung adenocarcinoma. In lung adenocarcinoma cells, the silencing/overexpression of YBX1 caused a simultaneous change in MUC1, and MUC1 overexpression partially reversed the decreased tumor cell migration, aggressiveness, and stemness caused by YBX1 silencing. Moreover, chromatin immunoprecipitation (ChIP) and dual-luciferase reporter assays proved that MUC1 was the downstream target of YBX1 and that YBX1 bound to the -1480~-1476 position in the promoter region of MUC1 to regulate its transcription. Furthermore, in mouse xenograft models and a lung cancer metastasis model, MUC1, which is downstream of YBX1, partially reversed the decreased number and size of tumors caused by YBX1 silencing. In conclusion, our findings indicated a novel mechanism by which YBX1 promotes the stemness and metastasis of lung adenocarcinoma by targeting MUC1 and provided a combination approach for diagnosis different from traditional single tumor biomarkers to predict patient prognosis and provide clinical treatment targets.